Change in streamflow response in unregulated catchments in Sweden over the last century. Issue 8 (5th August 2016) - Åkesson, Anna; Wörman, Anders; Riml, Joakim; Seibert, Jan
Abstract: A Fourier spectral analysis of daily discharge time series over the last century in 79 unregulated catchments in Sweden reveals a significant gradual steepening of the discharge power spectrum slope over time. Where historical meteorological observations are available (the 41 southernmost catchments), the results of our analyses indicate that local land use changes within the catchments have affected discharge power spectra to a greater extent than have changes in precipitation patterns. 1‐D distributed routing analysis based on current and historical maps and scenario modeling in the Törnestorp Catchment suggests that changes in stream network properties have led to increases in the hydraulic Péclet number ( P e ) and subsequent decreases in the discharge power spectrum over short periods. The analysis displays analytically how a change in stream network properties can result in changes in the power spectra, where the relative importance of the geomorphological and hydrodynamic dispersion effects determines the shape of the streamflow response. The lowering of the discharge power spectrum over short periods observed for many Swedish catchments is likely caused by increasing P e (a decrease in dispersion) over time, resulting in higher peak values, especially for rapid streamflow responses (i.e., over short periods), demonstrated empirically for the Törnestorp case study. The finding that the discharge power spectrum can change significantly over time highlights the need for hydrological models to account for the effect of the nonstationarity of parameters that result from temporal change caused by land use change and/or climate change that is due to anthropogenic or natural causes. Key Points: Hydrograph variance has decreased significantly over the last century at short periods (days) in unregulated Swedish catchments Decreased hydrodynamic dispersion is a cause of the steepened discharge power spectra in Swedish catchments over the last century Analytical and numerical analyses show connection between power spectra and hydrodynamic as well as geomorphological dispersion effects